Involvement of Heat Shock Protein 70 in the DNA Protective Effect From Estrogen. (May 2013) - Dong, Yilong; Wang, Yanmei; Yu, Haijing; Liu, Yanyong; Yang, Nan; Zuo, Pingping
As an endogenous cytoprotective factor, the protection of estrogen and heat shock protein-70 (Hsp70) on DNA has been documented, respectively, but the functional interaction between estrogen and Hsp70 on DNA damage repair is largely unknown. We therefore investigated the relation between estrogen and Hsp70 in terms of DNA protection in in vitro. The findings showed a significant reduction in cell survival and elevation in oxidative stress while cells were exposed to amyloid β (Aβ25-35 ) peptide, but preincubation of the cells with 17β-estradiol (17β-E2) ameliorated this situation. In addition, 17β-E2 alleviated oxidized DNA damage induced by Aβ and elevated the expression of Hsp70. However, the beneficial properties of 17β-E2 on reducing DNA damage were attenuated when Hsp70 gene was silenced accordingly. These results indicate that Hsp70 plays a role in DNA protection mediated by estrogen, and the DNA protection may be involved in Alzheimer's disease preventive effect from estrogen.